Application of User Experience Questionnaire Method to Evaluate Customer Experience When Conducting Transactions with Digital Wallets - Butar Butar, Ribka Sari; Dharmawan, Donny; Kalsum, Umi; Munizu, Musran; Mertha Agung Durya, Ngurah Pandji (SEULANGA SYSTEM PUBLISHER, 2023)
The purpose of this study is to determine how to use the user experience questionnaire (UEQ) to assess the digital wallet user experience. This research employs a quantitative methodology. In order to collect data for this study, surveys, observation, and literature reviews were used. All of the participants in this study are users of digital wallets. In this study, 100 samples were drawn using simple random sampling as the sampling technique. The two types of data analysis were statistical analysis and demographic analysis. The author examined demographic information first. Second, the author used the UEQ Data Analysis Tool to perform statistical analysis. Testing for validity and reliability was done at this point. The discussion's outcomes allow for the following deductions to be made: This study was successful in assessing how digital wallets performed across the board on the user experience questionnaire (UEQ). Based on evaluation findings using UEQ, this research was successful in offering suggestions for enhancing the user experience in digital wallets. The attractiveness and novelty parts of the user experience are the areas that are advised to be improved upon, since they continue to receive below-average benchmark scores.